Filología frente a traducción en la elaboración de un diccionario histórico - Carriscondo-Esquivel, Francisco M. (2010)
As a result of the analysis of the articles regarding agua and aire in the fascicles from the —failed— Diccionario histórico de la lengua española (1960-1996), I propose the necessity that the editor of the definitions in a work of this type should prefer and be inclined towards philology, rather than the translating of those experiences into ones closer to our current heritage of knowledge, because of the reflection —in the definitional text— of the experiences of the community of users of that term in a specific period. A semantic description of this kind will aid to improve the understanding of past realities and, as a later step, of how those realities were understood, by means of the lexis which designates those experiences.